2012
DOI: 10.1117/12.929685
|View full text |Cite
|
Sign up to set email alerts
|

Transparent conducting materials: overview and recent results

Abstract: An overview of different transparent conductors is given. In addition, atmospheric pressure CVD of ZnO resulted in conductivities below 1 mΩ cm for a temperature of 480°C, whereas at a process temperature of 200°C a value of 2 mΩ cm was obtained. Also atmospheric pressure spatial ALD was used to make conductive ZnO. Furthermore, the properties of transparent conductive oxides (TCO) can be enhanced by application of metallic grids. This way, sheet resistances of below 0.1 Ω/sq and transmittances above 85 % can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The best TCO material is a trade-off between the sheet resistance and the transmittance and depends on the device specific requirements. Figure 2b shows that when metallic grids and a TCO are combined, the sheet resistance can be improved at minimal transmittance losses compared with using a TCO or a thin metal film only [22]. Although this already suggests improved device performance, it should be noted that Figure 2b shows the result of a rectangular grid.…”
Section: Methodsmentioning
confidence: 92%
“…The best TCO material is a trade-off between the sheet resistance and the transmittance and depends on the device specific requirements. Figure 2b shows that when metallic grids and a TCO are combined, the sheet resistance can be improved at minimal transmittance losses compared with using a TCO or a thin metal film only [22]. Although this already suggests improved device performance, it should be noted that Figure 2b shows the result of a rectangular grid.…”
Section: Methodsmentioning
confidence: 92%
“…It was reported that the combination of a metallic grid and a TCO can result in a much higher conductivity, with only a small sacrifice in transmittance, see Fig. 2 (van Deelen et al, 2012;van Deelen et al, 2011b;van Deelen et al, 2014a). Because such approach would add complexity in the manufacturing process, the efficiency gain should be determined and evaluated with respect to manufacturing issues (Galagan et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…The width of these stripes is in part dictated by the quality of the front contact (Rowell and McGehee, 2011). This quality is expressed in the physical characteristics of transparency and conductivity (van Deelen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the possibility of accommodating earths abundant transition metals in different oxidation states at the O h and T d sites, spinels such as the CuFe 2 O 4 , GaZn 2 O 4 , CuCo 2 O 4 and SnMg 2 O 4, offer an excellent opportunities for designing many technological applications which include: transparent conducting oxides (TCOs), [7][8][9][10][11], humidity sensors, magnetic materials for spintronics and storage devices, redox materials for solar-thermal water splitting, high surface-reactivity catalysts for water-gas shift reactions, electrodes in lithium-ion as well as sodium-ion batteries, and hydrogen generation for microbial systems [12][13][14][15][16]. In a 'normal' XM 2 O 4 spinel-type oxide, all X cations occupy the O h sites while the M cations occupy T d sites, whereas, in an 'inverse' spinel-type, the O h sites are shared equally by X and M cations with the T d sites occupied only by X cations [17].…”
Section: Introductionmentioning
confidence: 99%